What Do Micro Price Data Tell Us on the Validity of the New Keynesian Phillips Curve? - Luis Julián Alvarez González (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
This paper surveys the current state of global empirical research on price setting behaviour at the firm level to evaluate the adequacy of pricing models used in the macro literature. To that end, it analyses the implications of 25 theoretical models (sticky information, menu costs, time dependent, costs of adjustment and customer anger models) in terms of their ability to match the key micro stylised facts. It is found that the explanatory power differs considerably across models and that many popular models are at odds with the main micro features, suggesting the need to further refine modelling strategies.
Keywords: E31; D40; 330; Pricing models; micro data; Phillips Curve; hazard rate; time dependent; menu costs; sticky information; New-Keynesian Phillips Curve; Betriebliche Preispolitik; Preisstatistik; Schätzung; Welt